Conceptualization of the psychological aspects of the normalization of gender-based violence against women during the escalation of war in Ukraine - Danyliuk, Ivan; Malysheva, Karine; Loshenko, Oleksandra; Burkalo, Nataliia; Yahiiaiev, Illia; Lytvyn, Serhii (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. The article focuses on the conceptualization of the psychological aspects underlying the normalization of gender-based violence against women during the escalation of war in Ukraine. A theoretical study was conducted to identify key social factors associated with changes in the readiness of victims and witnesses of violence—including combatants, civilian volunteers, and individuals residing in conflict zones – to report cases of gender-based violence or to seek help since the onset of the war’s escalation in Ukraine.                Methods. Theoretical research methods were applied, including the analysis of scholarly sources, comparison and synthesis of concepts, generalization and modeling.Results. The study examines attitudes toward invisible forms of gender-based violence against women and analyzes the social and cultural beliefs associated with the normalization of such violence. It was found that perceptions of invisible forms of gender-based violence against women are linked to several psychological constructs: ambivalent attitudes, coercive and utilitarian attitudes, and crisis-related attitudes. The process of normalization of gender-based violence against women is explored within the framework of gender-oriented microaggressions and ambivalent sexism theory. The study also identifies several social and cultural factors that contribute to this normalization, including: cultural beliefs about women’s responsibility for men’s behavior; internalized gender differences in relationships; cultural notions of male and female “biology”; societal pressure on women to prioritize family roles; conceptualizations of love; beliefs about “female strength”; pressure on women to remain focused on domestic spheres; and attitudes toward the acceptability of violence in certain areas of life.Conclusions. Attitudes toward invisible forms of gender-based violence against women, along with the social and cultural beliefs associated with its normalization, represent relevant psychological constructs for understanding the processes of normalization under conditions of war escalation in Ukraine. Identifying, critically analyzing, and replacing such beliefs with less discriminatory ones may serve as an important factor in counteracting the normalization of gender-based violence against women.
Keywords: gender-based violence against women; normalization of gender-based violence; invisible forms of gender-based violence; war in Ukraine